2009
DOI: 10.1002/pi.2590
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of redox initiators for free radical frontal polymerization

Abstract: BACKGROUND: The reaction temperature for frontal polymerization (FP) initiated by redox initiators can be greatly decreased compared with FP initiated by peroxide initiator and disulfide initiator. We report the synthesis of poly(hydroxyethyl acrylate)s via free radical FP using benzoyl peroxide (BPO)/N,N‐dimethylaniline (DMA) and ammonium persulfate (APS)/N,N,N′,N′‐tetramethylethylenediamine (TMEDA) couples as redox initiators at ambient pressure. RESULTS: The results show that unlike the phenomenon of bubble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“…Since the heat released from the FP reaction usually induces the boiling of certain solvents, solvents with high boiling point (e.g., DMSO, NMP and glycerol) were employed for producing samples in FP to avoid the formation of bubbles . The monomers DMC and HPA are water‐soluble, so we choose glycerol (boiling point: ∼290 °C) as solvent.…”
Section: Methodsmentioning
confidence: 99%
“…Since the heat released from the FP reaction usually induces the boiling of certain solvents, solvents with high boiling point (e.g., DMSO, NMP and glycerol) were employed for producing samples in FP to avoid the formation of bubbles . The monomers DMC and HPA are water‐soluble, so we choose glycerol (boiling point: ∼290 °C) as solvent.…”
Section: Methodsmentioning
confidence: 99%
“…Since the heat released from the FP reaction usually induces the boiling of certain solvents, solvents with high boiling point (e.g., DMSO, NMP, and glycerol) were employed for producing samples in FP to avoid the formation of bubbles . The monomer PMMA‐ b ‐PVI is oil‐soluble, so NMP (boiling point: ∼203 °C) was used as solvent.…”
Section: Methodsmentioning
confidence: 99%
“…The ability to prepare uniform materials in a fast fashion, and perhaps more importantly, to vary the morphology in a controlled manner, is in fact what makes FP attractive for many applications . Considering FP has advantages over traditional batch polymerization (BP) method in terms of reduced energy costs, reduced waste production, and unique morphology . As well, it have been reported that polyester–styrene resins prepared by FP achieved higher conversion than those fabricated by the usual BP .…”
Section: Introductionmentioning
confidence: 99%